The Use of Narratives in Business Models: a proposal to understand the logics of human action in entrepreneurship - Silva e Meirelles, Dimária; Thomaz, José Carlos (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2024)
This article aims to demonstrate how the narrative analysis method, combined with a value-based perspective of business model structuration, can be applied to identify the logic of human action in entrepreneurship. The business model is a narrative story, a form of presentation, explanation, or interpretation of elements that give meaning to the creation of business opportunities. However, not every element is explicit in the narratives of entrepreneurs who are showing, mainly to investors, how their business models are structured. Based on the mapping of implicit or explicit oppositions in the story, which enables the identification of hidden meaning in arguments, the logic of the narrative is extracted from the perspective of the dialectical process, where the sequence of events does not follow a chronological line but rather the outcome of the value creation, configuration, and appropriation process.